Increasing Reading Skills in Rural Areas: An Analysis of Three School Districts - Jean Stockard (Journal of Research in Rural Education, 2011)
Reviews of research on rural education suggest that identifying ways to help rural schools improve teachers' pedagogical skills should be a high priority. This article addresses this issue by examining changes in reading skills through the primary grades of students in three rural, Midwestern districts that occurred after the implementation of a highly structured and explicit reading curriculum (Reading Mastery) with implementation-associated support and guidance. Using a cohort control group design, reading skills of students who had the curriculum from the beginning of kindergarten (full exposure cohorts) were compared with those of students who began the curriculum in later years. By the middle of kindergarten, those in the full exposure cohorts had significantly higher DIBELS scores than students in the other cohorts and scores that were equal to or higher than a national sample. Differences remained strong and significant through grade 3, and effect sizes generally surpassed usual standards of educational significance. Data were available on scores on state reading examinations for fourth graders in one of the districts, and similar results were found. The findings illustrate how rural districts in a sparsely populated state can support teachers' pedagogical development and how this support can translate into higher student achievement.